Afetividade na residência integrada em saúde: o psicólogo no território de form"ação" - Feitosa, Maria Zelfa de Souza (2014)
Affection can be understood as the passage from one state to another power, which leads the body and mind, understood as a totality, the action or inaction. It is believed that the work of the psychologist in the area of public health policies, among other issues, is permeated by emerging affections of the encounter with the territory, and that the training contributes to how this action is effective. Therefore, our study aimed to analyze the impact of affectivity (emotions and feelings) in practicing psychologists-residents in public health policy, primary and secondary levels, from its contact with the area of services. For that, we choose as research locus Integrated Health Residency (RIS), linked to Escola de Saúde Pública do Ceará (ESP /CE) (School of Public Health of Ceará), in emphasis of the Family and Community Health and Mental Health Collective, interviewing 18 psychologists-residents inserted therein. In this attempt, were adopted as the main theoretical basis of social psychology Historic Cultural bases developed by Silvia Lane and colleagues, and Environmental Psychology. Characterized as a qualitative research, the data collection was performed by applying the qualitative part of the Instrument Generator Maps Affective, whose analysis was accomplished by analysis of Categorical Content and Analysis of subtext, of sense and reason; and semi-structured interviews, analyzed through qualitative analysis with the help of Atlas.ti software. The results obtained in the study showed an Esteem negative role in relation to the health service where psychologists work-residents, but shows a tendency to positive engagement with the territory - specifically the community and users - and the ideal of the service should be, giving a predominance of mixed picture on the maps, which denotes polarization of affect in relation to space, such as happiness / satisfaction and anxiety / fear. The interviews also reflected the predominance of images of contrasts in relation to academic background and contrasts and pleasantness related to RIS, pointing to a greater satisfaction with job training. The main activities carried out were related to the group, individual consultations and home visits activities. We hope that the research developed will contribute to the discussion of the practice of the psychologist in public health services and of the proposal of the Multidisciplinary Residency as in-service training.